RESULTS FROM A NATIONAL CROSS-SECTIONAL STUDY OF DISEASE BURDEN IN CROHN'S DISEASE. (21st January 2021) - Seabury, Jamison; Zizzi, Christine; Weinstein, Jennifer; Wagner, Ellen; Rosero, Spencer; Dilek, Nuran; Kaat, Aaron; McDermott, Michael; Saubermann, Lawrence; Temple, Larissa; Rogoff, Scott; Heatwole, Chad
Abstract: Background: Patients with Crohn's disease experience a wide variety of clinical symptoms that affect how they feel and function. As therapeutic trials are planned for patients with Crohn's disease, it is important to better understand the symptoms that have the greatest impact on Crohn's disease patient's lives. Objective: To identify the most common and important disease manifestations in Crohn's disease in a large population of patients. To determine the modifying factors that are associated with these symptoms. Methods: We conducted a national cross-sectional study of 415 patients from the IBD Partners patient registry sponsored by the Crohn's & Colitis Foundation to identify the prevalence and relative importance of 148 individual symptoms across 17 unique symptomatic themes. These themes were previously identified through 16 semi-structured qualitative interviews with Crohn's patients. Results: Crohn's disease participants provided over 55, 000 symptom rating responses. The symptomatic themes with the highest prevalence in Crohn's disease were gastrointestinal issues (93.0%), fatigue (86.4%), dietary restrictions (77.9%), impaired sleep or daytime sleepiness (75.6%), and inability to do activities (72.3%). Symptomatic theme prevalence was widely associated with having above the median number of stools per day, having above the median number of bowel movements per day, having perianal disease, having to miss work, and unemployment. Discussion/Conclusion: Crohn's disease symptoms, some under-recognized, vary based on disease characteristics and demographic features. These symptoms represent targets for future therapeutic interventions and are potential areas of interest for an upcoming disease-specific patient-reported outcome measure for this population. Acknowledgements: Funding for this project was provided by UR Ventures. Research activities were conducted in collaboration with the Crohn's & Colitis Foundation.